Toxic AGEs (TAGE) Cause Lifestyle-Related Diseases - Masayoshi Takeuchi (Antioxidants)
Advanced glycation end-products (AGEs) play a role in the onset/progression of lifestyle-related diseases (LSRD), suggesting that the suppression of AGE-induced effects can be exploited to prevent and treat LSRD. However, AGEs have a variety of structures with different biological effects. Glyceraldehyde (GA) is an intermediate of glucose, and fructose metabolism and GA-derived AGEs (GA-AGEs) have been associated with LSRD, leading to the concept of toxic AGEs (TAGE). Elevated blood TAGE levels have been implicated in the onset/progression of LSRD; therefore, the measurement of TAGE levels may enable disease prediction at an early stage. Moreover, recent studies have revealed the structures and degradation pathways of TAGE. Herein, we provide an overview of the research on TAGE. The TAGE theory provides novel insights into LSRD and is expected to elucidate new targets for many diseases.